2006
DOI: 10.1007/bf02905276
|View full text |Cite
|
Sign up to set email alerts
|

Agreement in depression determination among four self-rating depression scales applied to Japanese community-dwelling elderly

Abstract: Objective: In this study, we examined the characteristics of depression determination using four representative self-rating depression scales (Geriatric Depression Scale, GDS; Self-rating Depression Scale, SDS; Center for Epidemiologic Studies Depression Scale, CES-D; and Carroll Rating Scale, CRS) applied to Japanese community-dwelling elderly.Methods: Subjects were 563 community-dwelling independent elderly living in twelve prefectures (330 males, 68.9±6.3 yr; 233 females, 68.1±5.8 yr).Results: Depression ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
8
1
Order By: Relevance
“…SDS is a somewhat old scale, but has been translated into most languages, and especially Chinese and Japanese specialists in psychosomatic medicine often use it for rating depression even today [33][34][35]. Demura et al reported the correlation of depression scale scores between SDS and CES-D in 563 Japanese was significant and comparable (correlation coefficient: 0.78, p b 0.01), and similarities in depression determination were found between SDS and CES-D [36].…”
Section: Evaluation Of Depression and Anxietymentioning
confidence: 91%
“…SDS is a somewhat old scale, but has been translated into most languages, and especially Chinese and Japanese specialists in psychosomatic medicine often use it for rating depression even today [33][34][35]. Demura et al reported the correlation of depression scale scores between SDS and CES-D in 563 Japanese was significant and comparable (correlation coefficient: 0.78, p b 0.01), and similarities in depression determination were found between SDS and CES-D [36].…”
Section: Evaluation Of Depression and Anxietymentioning
confidence: 91%
“…Older people are vulnerable, as they often have multiple coexisting medical and psychological problems . In addition, depression is a common response to negative life events, such as being widowed or divorced, being retired, and loss of social role and network among older people . Depression decreases an individual's quality of life and increases dependence on others .…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization estimates that the worldwide prevalence of depression varies between 10% and 20% . Its prevalence among older people ranged from 3.6% to 30.6% in Brazil, China, Japan, Korea, Malaysia, Taiwan and the USA…”
Section: Introductionmentioning
confidence: 99%
“…9 Psychological testing of depression in elderly people has been performed mostly by the questionnaire method, typically using the Geriatric Depression Scale, Zung Self-Rating Depression Scale, Center for Epidemiologic Studies Depression Scale, and Carroll Rating Scale. 10 The Geriatric Depression Scale is a 30-item questionnaire developed specifically for the elderly; 11 it has been used frequently for the evaluation of depression in elderly people. 12 In addition, a 15-item short version of the Geriatric Depression Scale (GDS-15) has been developed for easier use, and it has been used in many previous studies.…”
Section: Introductionmentioning
confidence: 99%